MEASURES OF MANAGEMENT ACTIONS USED IN THE PROCESS OF IMPLEMENTATION OF THE INVESTMENT PROJECT (FOR EXAMPLE, THE CONSTRUCTION ORGANIZATIONS OF SAMARA REGION) - E. Savoskina; O. Burlakova (Вестник университета)
The article gives a description of the factors that are most significant in the Samara region - price hike of construction materials, reduced buying activity, which won't drastically increase construction and installation work, which means the construction industry during the next years will be in recession. The authors conducted the analysis of practical activities of construction organizations performing the functions of customer-builder and implementing projects with different funding schemes, which showed that the company for survival in the construction market is necessary to implement various projects and in its numerical strength to provide expertise in different areas. The organization should be included in the portfolio of projects funded from other sources, except for facilities financed from the budget.